Prevalence of diabetes mellitus and impaired glucose regulation in Spain: the Di@bet.es Study - Federico Soriguer; Albert Goday; Anna Bosch-Comas; Elena Bordiú; Alfonso L. Calle‐Pascual; Rafael Carmena; Roser Casamitjana; Luís Castaño; Conxa Castell; Martin Catala; Elías Delgado; Josep Franch‐Nadal; et al. (2011)
The Di@bet.es Study is the first national study in Spain to examine the prevalence of diabetes and impaired glucose regulation. A population-based, cross-sectional, cluster sampling study was carried out, with target population being the entire Spanish population. Five thousand and seventy-two participants in 100 clusters (health centres or the equivalent in each region) were randomly selected with a probability proportional to population size. Participation rate was 55.8%. Study variables were a clinical and demographic structured survey, lifestyle survey, physical examination (weight, height, BMI, waist and hip circumference, blood pressure) and OGTT (75 g). Almost 30% of the study population had some carbohydrate disturbance. The overall prevalence of diabetes mellitus adjusted for age and sex was 13.8% (95% CI 12.8, 14.7%), of which about half had unknown diabetes: 6.0% (95% CI 5.4, 6.7%). The age- and sex-adjusted prevalence rates of isolated impaired fasting glucose (IFG), isolated impaired glucose tolerance (IGT) and combined IFG–IGT were 3.4% (95% CI 2.9, 4.0%), 9.2% (95% CI 8.2, 10.2%) and 2.2% (95% CI 1.7, 2.7%), respectively. The prevalence of diabetes and impaired glucose regulation increased significantly with age (p < 0.0001), and was higher in men than in women (p < 0.001). The Di@bet.es Study shows, for the first time, the prevalence rates of diabetes and impaired glucose regulation in a representative sample of the Spanish population.